Exploring Safety Culture Maturity Models: A Systematic Review of Approaches, Assessment Elements, and Industrial Contexts - Imanudin, Achmad Farizal (Publikasi Indonesia, 2025)
The rate of work accidents in various industrial sectors still shows an alarming trend, so efforts to improve safety culture are an urgent need. One of the strategic approaches used to encourage gradual improvement of safety culture is through the implementation of the Safety Culture Maturity Model (SCMM). This study aims to conduct a systematic literature review (SLR) of various SCMM models that have been used in the context of cross-sectoral organizations. Of the 58 articles screened, 17 articles met the criteria, including models, assessment elements, and industry contexts. The results of the study show that the Hudson model is the most widely used model due to its conceptual strength and flexibility in various industries. Other models such as Flemming (HSE model), DuPont Bradley Curve, as well as the development of sector-specific models such as Food Safety Culture Maturity (FSCM) have also been found to be relevant according to organizational characteristics and the level of readiness of safety culture. Analysis of assessment elements shows that leadership commitment, safety communication, training, employee engagement, and risk management are the most dominant indicators used in measuring the level of maturity of safety culture. This study is expected to be an additional reference for practitioners and researchers in choosing appropriate and effective models for the transformation of safety culture in their organizations.